CMLHS pioneering UMP-German programme - Yanti Salina, Saari (Pusat Bahasa Moden dan Sains Kemanusiaan, 2010)
12 July 2010. Beginning July 2010, UMP offered a Dual Degree Programme in Mechatronics Engineering with Hochschule Karlsruhe Technik und WirWirtschaft (HsKA) University for the Faculty of Manufacturing Engineering and Technology Management (FKPPT).